On some Disputable Issues Related to the Defining of Derivational Transposition - Аврамова, Цветанка (Języki słowiańskie dziś: w kręgu kategorii, struktur i procesów, 2021)
This article focuses on some disputable issues related to the defining of derivational transposition in a narrow sense (i.e. syntactic derivation). The study questions the requirement for identity between the lexical meaning of the derivative and the generative word. It also examines which level the analysed phenomenon refers to – the level of onomasiological categories, derivational modes or derivational meaning. The article draws attention to the fact that even authors proceeding from the same theoretical foundations refer to different types of derivatives as cases of transposition. All these observations indicate the necessity of re-evaluating the semantic aspect of the existing definition of transposition.